Complete Genome Sequence of a Legionella longbeachae Serogroup 2 Isolate Derived from a Patient with Legionnaires’ Disease - Haviernik, Jan (Microbiol Resour Announc, 2020)
Legionella longbeachae is the predominant cause of Legionnaires’ disease (LD) in New Zealand. Although serogroup 2 (sg2) does not contain the most clinically significant strain, it is an important cause of disease. Here, we report the complete genome sequence of an sg2 isolate from a patient who was hospitalized with LD.